Development of environmental laws in India - Kanchi Kohli Manju Menon; Menon, Manju (UK, Cambridge, 2021)
"This book is an attempt at presenting a critical analysis of the close relationship between India's development post-independence and the formulation, enactment and implementation of environmental laws in the country. It will engage with the deeper implications of these laws - some of which were enacted by the British and the princely states pre-independence - and examine how they have a bearing on the socioeconomic and political ethos of the time. It will also trace recent developments in India's environmental laws and how their implementation impacts the environment, and the future of environment justice in this country. This work will examine the politics behind the enactment of these laws in the garb of protecting the environment. Certain laws which were implemented pre-independence by the British were aimed at making environmental resource a commodity - to expedite the extraction of timber, minerals and other resources. Though the scenario changed post-1970s; in the 42nd amendment to the Constitution in 1976, environment protection was made a part of the non-justiciable Directive Principles of State Policy - a fundamental duty of every citizen. This move of the government earned many accolades across socio-political sections, but one has to bear in mind the time-period during which it was implemented - the infamous Emergency regime. The book envisions to interpret the discourse of environmental laws in India along these lines. It will look at the developmental-protectionist nature of the laws and also at the politico-economic factors at play"--
Fundamentals of environmental law -- Institutions regulating India's environment -- Forest reservation and conservation -- Pollution control and prevention -- Environmental protection -- Wildlife and biodiversity conservation -- Ground and surface water extraction -- Land acquisition -- Climate change and policy frameworks -- Contemporary environmental law reforms.
Includes bibliographical references and index.
Keywords: Environmental law -- India; Forest conservation -- India; Wildlife conservation -- India; Pollution -- India; Climatic changes -- India; Environmental policy -- India